2015
DOI: 10.1177/0046958015610762
|View full text |Cite
|
Sign up to set email alerts
|

Length of Stay and Inpatient Costs Under Medicaid Managed Care in Florida

Jungwon Park

Abstract: This study examines the patterns of length of stay (LOS) and inpatient costs for both Medicaid managed care and nonmanaged care patients using data from Medicaid patients aged 18 to 64 years who were discharged from hospitals in Florida between 2006 and 2012. This study used pooled cross-sectional multilevel modeling. The results show that the type of Medicaid program in which patients were enrolled was significantly related to the hospital LOS and inpatient costs. Medicaid managed care patients had 7% shorter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Because there was no evidence of changes in quality among plans remaining in state markets (28), increases in Medicaid HMO market concentration may not necessarily harm Medicaid recipients. The only other study on this topic reported a negative association between the number of HMOs operating in the local area and hospital length of stay in Florida (41).…”
Section: Qualitymentioning
confidence: 98%
“…Because there was no evidence of changes in quality among plans remaining in state markets (28), increases in Medicaid HMO market concentration may not necessarily harm Medicaid recipients. The only other study on this topic reported a negative association between the number of HMOs operating in the local area and hospital length of stay in Florida (41).…”
Section: Qualitymentioning
confidence: 98%